Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18203/2349-2902.isj20173378
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for hepatocellular carcinoma in the caudate lobe: a report of 13 cases

Abstract: INTRODUCTIONPrimary hepatocellular carcinoma (HCC) is one of the most common digestive tract tumors, and surgical resection is the preferred therapeutic method of HCC. However, as caudate lobe is located in the middle of the back of liver, surrounded by a large number of large vessels, it is difficult and risky to resect.1 Many doctors attempted to adopt TACE-based non-operative method for the treatment of HCC located in the caudate lobe, but its clinical effects are controversial. In addition, with the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, they reported that HCCCL was associated with significantly more frequent intrahepatic recurrence and a poorer survival rate. Zhang et al 9 . reported similar findings of poorer prognosis of HCCCL patients.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In addition, they reported that HCCCL was associated with significantly more frequent intrahepatic recurrence and a poorer survival rate. Zhang et al 9 . reported similar findings of poorer prognosis of HCCCL patients.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, they reported that HCCCL was associated with significantly more frequent intrahepatic recurrence and a poorer survival rate. Zhang et al 9 reported similar findings of poorer prognosis of HCCCL patients. Moreover, Sakamoto et al 24 reported that, despite no significant decrease in survival, HCCCL was associated with a longer operative time and higher blood loss than HCC in other locations.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations